B is the correct answer R=Q-7s/4
Answer:
![\huge\boxed{(d+7)(d-7)=d^2-49}](https://tex.z-dn.net/?f=%5Chuge%5Cboxed%7B%28d%2B7%29%28d-7%29%3Dd%5E2-49%7D)
Step-by-step explanation:
![\bold{METHOD\ 1:}\\\\(d+7)(d-7)\qquad|\text{use}\ (a+b)(a-b)=a^2-b^2\\\\=d^2-7^2=d^2-49\\\\\bold{METHOD\ 2:}\\\\(d+7)(d-7)\qquad|\text{use FOIL}\ (a+b)(c+d)=ac+ad+bc+bd\\\\=(d)(d)+(d)(-7)+(7)(d)+(7)(-7)\\\\=d^2-7d+7d-49\qquad|\text{combine like terms}\\\\=d^2+(-7d+7d)-49\\\\=d^2-49](https://tex.z-dn.net/?f=%5Cbold%7BMETHOD%5C%201%3A%7D%5C%5C%5C%5C%28d%2B7%29%28d-7%29%5Cqquad%7C%5Ctext%7Buse%7D%5C%20%28a%2Bb%29%28a-b%29%3Da%5E2-b%5E2%5C%5C%5C%5C%3Dd%5E2-7%5E2%3Dd%5E2-49%5C%5C%5C%5C%5Cbold%7BMETHOD%5C%202%3A%7D%5C%5C%5C%5C%28d%2B7%29%28d-7%29%5Cqquad%7C%5Ctext%7Buse%20FOIL%7D%5C%20%28a%2Bb%29%28c%2Bd%29%3Dac%2Bad%2Bbc%2Bbd%5C%5C%5C%5C%3D%28d%29%28d%29%2B%28d%29%28-7%29%2B%287%29%28d%29%2B%287%29%28-7%29%5C%5C%5C%5C%3Dd%5E2-7d%2B7d-49%5Cqquad%7C%5Ctext%7Bcombine%20like%20terms%7D%5C%5C%5C%5C%3Dd%5E2%2B%28-7d%2B7d%29-49%5C%5C%5C%5C%3Dd%5E2-49)
Answer:
B
Step-by-step explanation:
-10 + 3x - x - 7x + 5x + 7 + 2x
combine like terms
-10 + 3x - x - 7x + 5x + 7 + 2x
-3 + 3x - x - 7x + 5x + 2x
the -7x and the 5x + 2x cancel out to 0, so for the x terms we are left with 3x -x to get 2x
= 2x - 3
Answer:The equation of the parabola is y=18(x−2)2−3